Biofilm-Induced Type 2 Innate Immunity in a Cystic Fibrosis Model of Pseudomonas aeruginosa - Bielen, Kenny; ‘S Jongers, Bart; Boddaert, Jan; Raju, Tom K.; Lammens, Christine; Malhotra-Kumar, Surbhi; Jorens, Philippe G.; Goossens, Herman; Kumar-Singh, Samir (Frontiers in Cellular and Infection Microbiology, 2017)
Biofilm-producing strains of Pseudomonas aeruginosa are a major cause of morbidity and mortality in cystic fibrosis (CF) patients. In these patients, increased levels of IL-17 as well as of IL-5 and IL-13 along with arginase (Arg)-positive macrophages have been observed in bronchoalveolar lavage fluid. While IL-17 is a strong proinflammatory cytokine associated with host defense against bacterial and fungal infections and is also elevated in several autoimmune diseases, IL-5/IL-13 and Arg1-positive M2 macrophages are part of the anti-inflammatory type 2 (Th2) immunity. To study whether increased IL-5 and IL-13 levels are related to biofilm formation, which is frequently observed in CF patients colonized by P. aeruginosa, we utilized an agarose bead-embedded P. aeruginosa rat model commonly employed in in vivo biofilm studies. We showed that “sterile” agarose bead instillation in rat notably increased lung transcript levels of IL-5 and IL-13 at two post-instillation study-points, day 1 and day 3. Concurrently, increased infiltration of type 2 innate cells such as eosinophils and Arg1 positive M2 activated macrophages (Arg1+CD68+) was also observed both at day 1 and day 3 while the proportion of M1 activated macrophages (iNOS+CD68+) at these time-points decreased. In contrast, P. aeruginosa-loaded beads caused a drastic elevation of proinflammatory Th1 (IFNγ, TNFα, IL-12a) and antibacterial Th17 (IL-17a, IL-17f, IL-22, IL-23a) cytokines along with a high influx of neutrophils and M1 macrophages, while Th2 cytokines (IL-5 and IL-13) drastically declined at day 1 post-infection. Interestingly, at day 3 post-infection, both Th1 and Th17 cytokines sharply declined and corroborated with decreased M1 and increased M2 macrophages. These data suggest that while IL-17 is linked to episodes of acute exacerbations of infection in CF patients, the increased Th2 cytokines and M2 macrophages observed in these patients are largely due to the biofilm matrix. The data presented here has important implications for clinical management of CF patients.